MECHANISMS FOR DEVELOPING CULTURAL DIPLOMACY BETWEEN THE REPUBLICS OF KYRGYZSTAN AND TAJIKISTAN (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2026)
In this article, author examines the mechanisms for developing cultural diplomacy between the Kyrgyzstan and Tajikistan as a strategic instrument for enhancing bilateral relations, fostering social cohesion, and mitigating conflict risks in a historically sensitive border context. Methodologically, the article employs qualitative analysis of policy documents, bilateral agreements, and regional cooperation frameworks, complemented by comparative insights from Central Asian diplomatic practice. The findings identify key institutional, societal, and discursive mechanisms shaping Kyrgyz–Tajik cultural diplomacy, including intergovernmental cultural commissions, educational and academic exchanges, joint heritage and language initiatives, people-to-people diplomacy, and the role of civil society and local communities in border regions. Particular attention is given to the integrative potential of shared historical narratives, cross-border cultural events, and youth-oriented programs in counteracting securitization and politicization of identity. The article argues that effective cultural diplomacy requires institutional continuity, depoliticization of cultural cooperation, and alignment with broader regional confidence-building measures.